Dressing Constitutionally : Hierarchy, Sexuality, and Democracy from our Hairstyles to our Shoes - Robson, Ruthann (Cambridge University Press, 2013)
This book examines how the intertwining of clothes and the United States Constitution raises fundamental questions of hierarchy, sexuality and democracy. Constitutional considerations both constrain and confirm daily choices. In turn, appearances provide multilayered perspectives on the Constitution and its interpretations. Garments often raise First Amendment issues of expression or religion, but they also prompt questions of equality on the basis of gender, race and sexuality. At work, in court, in schools, in prisons and on the streets, clothes and grooming provoke constitutional controversies. Additionally, the production, trade and consumption of apparel implicates constitutional concerns including colonial sumptuary laws, slavery, wage and hour laws, and current notions of free trade. The regulation of what we wear - or do not - is ubiquitous. From a noted constitutional scholar and commentator, this book examines the rights to expression and equality, as well as the restraints on government power, as they both limit and allow control of our most personal choices of attire and grooming.